Efficient Mobility Using Multicast Routing Mechanisms - Babu, V. Ganesh (International Journal of Computer Sciences and Engineering, 2013)
One of the most important metrics in the design of IP mobility protocols is the handover performance. Handover occurs when a mobile node changes its network point-of attachment from one access router to another. If not performed efficiently, handover delays, jitters and packet loss directly impact and disrupt applications and services. With the Internet growth and heterogeneity, it becomes crucial to design efficient handover protocols that are scalable, robust and incrementally deployable. The current Mobile IP (MIP) standard has been shown to exhibit poor handover performance. Most other work attempts to modify MIP to slightly improve its efficiency, while others propose complex techniques to replace MIP.